Assessment of vascular age and cardiovascular risk factors among young women in the Moscow region - T. K. Chernyavskaya; S. N. Erofeeva (Российский кардиологический журнал)
Aim. To assess vascular age (VA) and the main cardiovascular risk factors (chronological age, body mass index (BMI), carotid-femoral pulse wave velocity (PWV), blood pressure (BP)) in women in the Moscow region.Material and methods. We assessed BP levels, BMI, PWV, and also calculate vascular age for women participating in the forum. BMI was calculated using the Quetelet index as weight divided by height squared (BMI=kg/m2). BP levels were measured in a sitting position three times on both arms, with the highest result recorded. PWV and vascular age were calculated using AngioScan01. The association between anthropometric measures, vascular stiffness, and VA differences was examined using multivariate linear regression, adjusting for traditional cardiovascular risk factors. Intergroup (systolic blood pressure <140 mm Hg and ≥140 mm Hg) comparisons of PWV and VA difference from actual were performed using a modified Welch's t-test.Results. The study involved 260 women. The mean age was 44,92±0,85 years (95% confidence interval (CI) 43,27-46,57), mean vascular age — 45,90±1,01 (95% CI 43,91-47,89), mean BMI — 23,383±0,66 kg/m2 (95% CI 22,046-24,720). Mean systolic BP was 127,63±1,89 mm Hg (95% CI 123,89-131,36), diastolic BP 80,031±0,93 (95% CI 78,20-81,86), mean PWV was 11,38±0,16 m/sec (95% CI 11,05-11,70). Analysis of the VA difference between women with BMI <25 kg/m2 (BMI1, n=93) and ≥25 kg/m2 (BMI2, n=67) revealed a significant difference in the calculated VA values (p=0,0002) between groups.Conclusion. Modern young women have high rates of vascular stiffness, which may determine the increase in morbidity and mortality rates in the working-age female population. The VA indicator predicts cardiovascular events and can be considered as an effective screening method for assessing cardiovascular risk, which is especially important for young patients.